基于有限元的轴承参数变化对离心式压缩机转子固有特性的影响研究 - 韩天; 史琳; 张庆海 (Jixie chuandong)
A rotor dynamics finite elementmodel of large centrifugal compressor is established by the finite element software.Based on thismodel,the different effects on the compressor rotor system natural vibration characteristic of bearing parameters are studied including lubricant oil temperature,clearance ratio and length-diameter ratio.